Implication of glutathione stransferases gene variants on acute intermittent porphyria onset - Pagnotta, Priscila Ayelén (2019)
Acute Intermittent Porphyria (AIP) is a result of a partial and primary deficiency in Porphobilinogen deaminase (PBG-D), the third enzyme in the heme pathway. The presence of the mutation is not enough for the manifestation of AIP that can be triggered by therapeutic drugs, so genetic variants in cell detoxification system could be involved in AIP onset. Glutathione-S-transferases (GST) are Phase II enzymes involved in detoxification of reactive oxygen species, environmental carcinogens, metabolism of steroid hormones and chemotherapeutic agents. Some polymorphisms in this gene affect GST activity, acting on the level of hormones and xenobiotics: GSTT1 null, GSTM1 null and GSTP1 (rs1695, c.313 A>G). The aim was to analyze these risk variants in relation with AIP onset. The study was performed in Control individuals (non porphyric) and in AIP patients carrying PBG-D mutation that at the moment of the diagnosis were symptomatics (S-AIP) or without clinical/biochemical manifestations (latent group, L-AIP). GSTT1 and GSTM1 were amplified by multiplex PCR, and GSTP1 variant by PCR-RFLP.The homozygote deletion frequencies for GSTT1 null were: 8.3% (Control), 20.5%(sAIP), 6.1% (lAIP) and 10.5% (PCT). Frequencies for GSTM1 null were: 41.7% (Control), 51.3% (sAIP), 45.5% (lAIP).GSTP1allelic frequencies for non-wild type (G) variant were: 0.42 (Control), 0.47 (S-AIP), 0.35 (L-AIP); genotypic frequencies were: AA: 29.2%, AG: 58.3% and GG: 12.5% (Control); AA: 33.3%, AG: 38.5% and GG: 28.2% (S-AIP); AA: 30%; AG: 70% and GG: 0% (L-AIP); and AA: 25%, AG: 60% When the combination of risk alleles were calculated, results showed: 0 alleles: 45.5%, 1 allele: 45.5%, 2 alleles: 9% and 3 alleles: 0% (Control); 0: 27%, 1: 46%, 2: 24.3% and 3: 2.7% (sAIP); and 0: 50%, 1: 50%, 2: 0% and 3: 0% (lAIP). In S-AIP, null GSTT1 was significantly high respect to control (p<0.05) and L-AIP (p<0.01); GSTM1 gene frequency were higher but no significant than the other cohorts. GG genotype frequency was significantly high for the GSTP1 respect to others groups (p< 0.01). A high frequency for the presence of 2 risk alleles was observed for the sAIP group with respect to L-AIP and Control. These results suggest a possible implication of GSTM1, GSTT1 and GSTP1 in the manifestation of AIP.